KEISTIMEWAAN PENDIDIKAN ISLAM DAN TIPOLOGI PENDIDIK IDEAL DALAM AL-QURAN DAN HADIS - Rangga Sa'adillah S.A.P.; Dewi Winarti; Daiyatul Khusnah (Piwulang: Jurnal Pendidikan Agama Islam, 2021)
This article seeks to describe two important terms in Islamic education, namely how the specialty of Islamic education is and what is the typology of ideal educators. These two important terms are described based on the authoritative sources of Islamic teachings, namely the Al-Quran and Hadith. The specialty of Islamic education can be parsed from the root word which refers to three terms, namely tabiyah, ta'lim, and ta'dib. From several terms regarding education and teaching, there are three discourses, namely: tarbiyah, ta'lim, ta'dib but have the same thing and the same goals. The term educator in Islamic education is often referred to by several terms including murabbi, mu'allim, muaddib. Apart from these three fairly popular terms, several terms are also used to refer to the word educators such as ustaz, murshid, and mudarris. Some of these words have their depth of meaning and usage.